Awakening Islam : the politics of religious dissent in contemporary Saudi Arabia - Lacroix, Stéphane, 1978- (Harvard University Press, 2011)
Amidst the roil of war and instability across the Middle East, the West is still searching for ways to understand the Islamic world. Stéphane Lacroix has now given us a penetrating look at the political dynamics of Saudi Arabia, one of the most opaque of Muslim countries and the place that gave birth to Osama bin Laden. The result is a history that has never been told before. Lacroix shows how thousands of Islamist militants from Egypt, Syria, and other Middle Eastern countries, starting in the 1950s, escaped persecution and found refuge in Saudi Arabia, where they were integrated into the core of key state institutions and society. The transformative result was the Sahwa, or "Islamic Awakening," an indigenous social movement that blended political activism with local religious ideas. Awakening Islam offers a pioneering analysis of how the movement became an essential element of Saudi society, and why, in the late 1980s, it turned against the very state that had nurtured it. Though the "Sahwa Insurrection" failed, it has bequeathed the world two very different, and very determined, heirs: the Islamo-liberals, who seek an Islamic constitutional monarchy through peaceful activism, and the neo-jihadis, supporters of bin Laden's violent campaign. Awakening Islam is built upon seldom-seen documents in Arabic, numerous travels through the country, and interviews with an unprecedented number of Saudi Islamists across the ranks of today's movement. The result affords unique insight into a closed culture and its potent brand of Islam, which has been exported across the world and which remains dangerously misunderstood